Coping Strategies in Household Financial Management among Families with Limited Economic Conditions - Tuti Handayani Zebua; Christian Slamat Silalahi; Rizky Peranginan Angin; Uswatun Hasanah (Jurnal Akuntansi dan Bisnis Syariah, 2026)
This study aims to understand coping strategies in household financial management among families with limited economic conditions. The study focuses on how families make financial decisions when facing economic pressure, such as increasing children’s needs, education costs, health expenses, and household expenditures that are not balanced with income. This research employs a descriptive qualitative approach. Data were collected through interviews with three housewives who had experience managing family finances under limited financial conditions. The data were analyzed through data reduction, data display, and conclusion drawing by grouping the informants’ responses into key themes. The findings show that household financial coping strategies are carried out by reducing consumptive spending, adjusting daily expenses, postponing certain purchases, using savings, preparing expenditure details, and seeking financial assistance from family members. In certain situations, online loans also emerge as a last alternative when family support is unavailable. These findings indicate that household financial management is not merely related to economic calculation, but also involves behavioral considerations, social relations, and the family’s ability to adapt to financial pressure. This study contributes to a broader understanding of household financial practices as everyday financial behavior that plays an important role in maintaining family economic sustainability.